Subunit stoichiometry of human Orai1 and Orai3 channels in closed and open states - Demuro, Angelo (National Academy of Sciences, 2011)
We applied single-molecule photobleaching to investigate the stoichiometry of human Orai1 and Orai3 channels tagged with eGFP and expressed in mammalian cells. Orai1 was detected predominantly as dimers under resting conditions and as tetramers when coexpressed with C-STIM1 to activate Ca(2+) influx. Orai1 was also found to be tetrameric when coexpressed with STIM1 and evaluated following fixation. We show that fixation rapidly causes release of Ca(2+), redistribution of STIM1 to the plasma membrane, and STIM1/Orai1 puncta formation, and may cause the channel to be in the activated state. Consistent with this possibility, Orai1 was found predominantly as a dimer when coexpressed with STIM1 in living cells under resting conditions. We further show that Orai3, like Orai1, is dimeric under resting conditions and is predominantly tetrameric when activated by C-STIM1. Interestingly, a dimeric Orai3 stoichiometry was found both before and during application of 2-aminoethyldiphenyl borate (2-APB) to activate a nonselective cation conductance in its STIM1-independent mode. We conclude that the human Orai1 and Orai3 channels undergo a dimer-to-tetramer transition to form a Ca(2+)-selective pore during store-operated activation and that Orai3 forms a dimeric nonselective cation pore upon activation by 2-APB.